The Predictive Role of Social Support on Attachment Styles Among Young Adults - Olubunmi James; Emmanuel Uye; Comfort Atota (CV. Dalle’ Deceng Abeeayla, 2026)
Social support contributes to attachment security over time. While studies have used different factors to predict attachment styles with varied results, there seem to be few studies using social support to predict attachment styles especially in the Nigerian settings. Therefore, this study examines the predictive role of social support on attachment styles among young adults. The study adopted cross-sectional survey using purposive sampling technique to select five communities in Port Harcourt metropolis in Rivers State, Nigeria. Data were collected from 277 using validated questionnaires and analyzed with simple linear regression to test one hypothesis that was accepted at p <.001 level of significance. The result demonstrated that social support significantly influenced attachment styles among young adults, F (1,276) = 21.34, p < .001. Moreover, the result indicated that social support independently predicted attachment styles among study participants (β = .421, t = 4.62, p < .001). The novelty of this study is that it the first time social support has been used to predict attachment styles among the study samples. The study recommends that young adults should actively build and maintain strong social support networks that would help them cope with challenges originating from poor attachment styles.